SOCCER SCORE WITH STEM! - Kelley, K. C. (Sports STEM, 2022)
"The soccer player smacks the ball with the inside of their foot, spending it spinning toward its target. It curves around the goalie and into the top corner of the net. Goal! Any good soccer player needs skill, practice, and a little bit of STEM. Explore the science, technology, engineering, and math behind the game of soccer. Sports and STEM? Score!"--